Comparative data compression techniques and multi-compression results - Ibrahimy, Muhammad Ibn; Motakabber, S. M. A. (2013)
Data compression is very necessary in business data processing, because of the cost savings that it offers and the large volume of data manipulated in many business applications. It is a method or system for transmitting a digital image (i.e., an array of pixels) from a digital data source to a digital data receiver. More the si ze of the data be smaller, it provides better transmission speed and saves time. In this communic ation, we always want to transmit data efficiently and noise freely. This paper will provi de some compression techniques for lossless text type data compression and comparative result o f multiple and single compression, that will help to find out better compression output and to dev elop compression algorithms.